In vitro effect of fiber reinforcement on fracture resistance of incisal edge composite restorations - Amin Salehi, Ebrahim; Ghorbani, Mahour; Hassani, Ramona; Amirzadeh, Zohreh (Journal of Dental School, 2019)
Objective: Introduction of fiber-reinforced composites (FRC) greatly enhanced the restoration of fractured anterior teeth. The purpose of this study was to assess the effect of fiber reinforcement on fracture resistance of incisal edge composite restorations of variable thicknesses. Methods: Forty extracted sound human maxillary incisors were divided into four groups of 10. Incisal reduction was done by 3mm in groups 1 and 3 and by 4mm in groups 2 and 4. Incisal edge was restored with hybrid composite in groups 1 and 2 and hybrid composite reinforced by two Ribbond fibers in the palatal surface in groups 3 and 4. All specimens were mounted in acrylic blocks, stored in saline solution and thermocycled. The teeth were then subjected to static load by universal testing machine until fracture. The load was applied at 135° angle relative to the tooth surface to an area2mm apical tothe incisal edge at a crosshead speed of 1mm/min. Data were analyzed using Tukey’s test and p≤0.05 was considered significant. Results: The mean fracture resistance was 436 (242) N, 492 (195) N, 992 (275) N and 1080 (236) N in groups 1 to 4, respectively and the difference in this regard among the 4 groups was statistically significant (p=0.000). The mean fracture resistance in group 3 (fiber-reinforced, 3mm thickness) was higher than that in group 1 (no fiber, 3mm thickness). This value in group 4 (fiber-reinforced, 4 mm thickness) was also higher than in group 2 (no fiber, 4mm thickness). The highest fracture resistance was seen in group 4.Thickness of composite had no significant effect on fracture resistance (p=0.347). Conclusion: Application of two Ribbond fibers can significantly increase the fracture resistance of incisal edge composite restorations.